Chemical potential of an ion in an asymmetric electrolyte within the mean spherical approximation (MSA). (17th December 2021) - Høye, Johan S.; Simonin, Jean-Pierre
Abstract : We study the known solution of the mean spherical approximation (MSA) for the primitive model of an electrolyte consisting of charged hard spheres with unequal diameters. Especially, details of the non-trivial evaluation of chemical potentials are given. They can be obtained in various independent ways from the known MSA solution. The different ways of evaluation are utilised to show that consistent results are obtained. Details for other thermodynamic quantities are also presented. An additional purpose of this rederivation of results is to give a firmer basis and insight to obtain the correct and consistent thermodynamics for the more demanding and realistic situation with polar particles present in the MSA electrolyte. GRAPHICAL ABSTRACT: UF0001